A Study of Servicescape and Component of Tourism Attractions Affecting the Intention to Stay in Accommodation in Nakhon Sawan Province - Tangchittaworngul, Panachakorn; Booranavitayaporn, Suphicha (Dusit Thani College Journal, 2022)
The purposes of this research were (1) to study the differences in the intention to stay in accommodation in Nakhon Sawan province as classified by demographic factors (2) to study how servicescape affects the intention to stay in accommodation in Nakhon Sawan province, and (3) to study the components of tourism attractions affecting the intention to stay in accommodation in Nakhon Sawan province. The sample group of this research consisted of 200 participants who had never stayed in accommodation in Nakhon Sawan province. This research was a Quantitative Research using a questionnaire as a data collection instrument. Data collection and analysis involved using statistics to indicate percentage, mean, standard deviation, t – test, One – Way ANOVA and multiple regression analysis. The results indicated that the majority of participants were female between 18 – 30 years old and 41 -50 years old with diploma/bachelor’s degree working in private companies and earning 15,001 – 30,000 baht monthly income on average. The first hypothesis test illustrated that there was only one demographic factor, which is occupation that influenced the intention of staying in accommodation in Nakhon Sawan province. For other hypotheses, servicescape including sign symbols and artifacts, and the tourism attractions including activities affected the intention to stay in accommodation in Nakhon Sawan province at a statistically significant level of 0.05.